Model Pengelolaan Dana KUM (Kredit Usaha Mandiri) oleh Petani Perempuan di Subak Guama, Tabanan Bali - ASTITI, NI WAYAN SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
KUM Fund Management Model (Independent Business Credit) by Women Farmers in Subak Guama, Tabanan Bali This research aims to describe the utilization model of KUM (Kredit Usaha Mandiri or Independent Business Credit) funds by female farmers, identify the types of businesses developed, and understand the profiles of female farmers managing KUM funds in Subak Guama. Data was collected through structured interviews, online (WhatsApp) interviews, and documentary studies. The respondents consisted of 25 female farmers who participated in the utilization of KUM credit in KUAT Subak Guama, selected through proportional random sampling. Data analysis was conducted using descriptive-interpretive, qualitative, and quantitative approaches. The research findings indicate that the KUM fund management model includes the utilization of credit as productive business capital by 67%, while 33% of the KUM funds are used for consumptive or non-productive purposes. The types of businesses developed include primary, secondary, and tertiary businesses. The profile of the female farmers consists of an average age of 46.48 years, an average education level of 10.56 years, a family burden of 4 individuals, and an average land ownership of 32.28 ares.